Human Fitrah in Family Education - Adkha Bukhori (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2018)
This research aims to describe and provide an explanation about the concept of human nature in the verses of Al-Qur’an and Hadith, and the implications of human nature in family education. This condition is motivated by the essence of Islamic values that highly appreciate the human dignity, especially the nature that has been brought human from birth. In addition, the family environment is the first place a child receives education. This research method using research library. Data collection is descriptive-interpretive. The results of the study in this study are (1) fitrah (human nature) as the basic human potential that has goodness and purity to receive the influence from outside to the truth, (2) the success rate of teaching value depends on the education process in the family, and (3) factors causing the problem are demands for economic fulfillment, lack of understanding of knowledge and technological developments, and weakness of values.